Variation of water-soluble carbohydrates and grain yield in Iranian cold barley promising lines under well-watered and water stress conditions - Mohammadi, Soleiman; Nazani, Reza Kas; Mahootchi, Ayda Hosseinzadeh; Ftohi, Keiwan (Plant Breeding and Seed Science, 2013)
In order to evaluate promising lines in terms of grain yield and water-soluble carbohydrates remobilization, an experiment with fifteen promising lines and two checks was carried out under full irrigation and terminal water stress conditions at Miyandoab Agricultural Research and Natural Resources Station. Mobilized dry matter content and remobilization percentage from shoot to grain under water deficit (177mg)(11.2%) were greater than those under well watering condition. The lowest (110 mg) and the highest (260mg) mobilized dry matter to grain were obtained for C-79-18 and C-83-15lines, respectively. Water deficit reduced grain yield of barley genotypes by 200-1600 kg/ha, and mean grain yield reduction was 800 kg/ha. Line 14 with 5.880and 5.300t/ha grain yield in favorable and water stress conditions was superior to the other lines. Under water deficit condition, line 14 had greater grain yieldby20% and 38% than the Bahman and Makouee cultivars, respectively. The results showed that greater grain yield in tolerant lines under water deficit was due to remobilization of unstructured carbohydrates from shoot to grain.Thus, it seems that selection of lines with higher translocated dry matter and contribution of pre-anthesis assimilate in grain filling under water stress, the suitable way for achieving genotypes with high grain yield under water stress condition.